Associations between physical performance and golf shot data: a pilot study of touring professional female players - Robinson, L.; Murray, A.; Glover, D.; Coughlan, D.; Mountjoy, M.; Scott, F.; Turner, A.; Bishop, C. (The Journal of Strength and Conditioning Research, 2025)
This study examined the relationship between a comprehensive physical testing battery and golf shot data in touring professional female golfers. Nineteen players (age: 31.00 ± 5.64 years; height: 170.84 ± 7.24 cm; body mass: 67.74 ± 9.16 kg; wingspan: 127.37 ± 14.21 cm) volunteered to take part in the study. Each player completed a dynamic warm-up before engaging in a 90-minute testing session, which gathered information on both physical capacity and golf shot data, all of which was collected at a single Ladies European Tour event. Golf shot data included clubhead speed, ball speed, carry distance, and smash factor, using a Trackman 4 launch monitor. Physical testing included anthropometry data, seated thoracic rotation, isometric mid-thigh pull (IMTP), isometric bench press, countermovement jump (CMJ), and seated medicine ball throws for distance. Pearson`s r correlations showed the CMJ to have the strongest and most consistent associations with golf shot performance (r = 0.51-0.60). In addition, force at 100 ms during the IMTP also demonstrated large associations with carry distance (r = 0.59), further highlighting the significance of rapid force production in the lower body. Collectively, the findings demonstrate the importance of lower body ballistic force production for female golfers, providing important information for practitioners regarding the relevant physical capacities for testing and training.